Biology in the laboratory - Helms, Doris R. (New York W. H. Freeman and Co., 1998)
Provides a choice of 46 laboratory topics and more than 200 experiments. Includes a diversity of instructional approaches, including simple guided inquiries, more complex experimental designs, and original student investigations.
Includes CD-ROM simulations.
Keywords: Biology -- Laboratory manuals